Pruning and Fruit Thinning of Psidium guajava cv. Paluma under a Seasonal Tropical Climate - Adaniel Sousa dos Santos; Jonathan Candido Thomaz Dalzot; Gustavo Alves Pereira; Jenilton Gomes da Cunha; Thamyres Yara Lima Evangelista; Wéverson Lima Fonseca; Murilo de Sousa Almeida; Julian Junior de Jesus Lacerda; Júlio Ferreira de Souza Filho; Alan Mario Zuffo; Ricardo Mezzomo; Jorge González Aguilera; et al. (Agriculture, 2023)
Maintaining the plant architecture of Psidium guajava L. (guava tree) is essential for enhancing capture and distribution in the plant, directly affecting the fruit quality. The lifespan of the harvest period can be extended by proper pruning. Both timeliness and proper pruning play crucial roles in achieving high-quality fruit production and in maintaining a consistent fruit size while stimulating ascorbic acid levels, sugar content, total soluble solids (TSS), and titratable acidity. From this perspective, this study aimed to characterize the influence of different intensities of fruit pruning and thinning on guava trees grown under a seasonal tropical climate in two growing seasons in Currais, Piauí, Brazil. The experiment was set up in a randomized block design with a 3 × 3 × 2 factorial arrangement corresponding to short, medium, and long pruning intensities and 0%, 10%, and 20% thinning intensities during the two growth seasons, respectively. An analysis was performed to discriminate the treatment groups according to the physicochemical variables of the guava tree cv. Paluma and canonical discriminant analysis. There was significant variation in the SS, titratable acidity, ascorbic acid, and pH contents. Cluster analysis of all treatments allowed division into five different groups for the two pruning times. Canonical discriminant analysis showed that the first two canonical variables explained 91% of the total variance. The fruits of the second harvest exhibited a lower level of acidity, higher levels of soluble solids, and higher levels of ascorbic acid contents. In addition, these fruits also obtained better nutrient contents. Short pruning with up to 20% thinning, medium pruning with up to 10%, and long pruning without thinning favored better levels of macronutrients and micronutrients and, consequently, better fruit quality. Medium or long pruning with up to 20% thinning resulted in higher average fruit weights and nutrient contents (especially of Fe and Cu), lower acidity, and higher ascorbic acid contents. Thus, in general, the importance of production pruning in guava plants is evidenced and thinning of 20% is recommended to improve the fruit quality.